PENGARUH SERVICESCAPE TERHADAP KEPUASAN PENGUNJUNG BULELENG FESTIVAL DI KABUPATEN BULELENG - I Nengah Wirata (JURNAL KEPARIWISATAAN, 2020)
The tourism sector is a mainstay sector that contributes or contributes significantly financially to the business activities of festival events in Bali Province. One of the districts that has carried out festival activities several times and has interesting natural and cultural attractions is Buleleng Regency. The Buleleng Regency Government holds festival events, one of which is the Buleleng Festival. The holding of the Buleleng Festival is a representation of bringing back local culture that can evoke the identity of Buleleng Regency. The local culture of Buleleng Regency is applied in a form of festival event activities. One of the festival events that is attractive to visitors' choice is the Buleleng festival. The Buleleng festival is a festival event that prioritizes attractive event design and concepts. The increasing number of festival events that are being held in Buleleng Regency, requires event planners and managers to have creative, innovative imaginations in presenting the concept of events by paying attention to various servicescapes and activities to increase the attraction and interest of visitors. The research objective is to examine how servicescape influence the visitor satisfaction of Buleleng festival. The number of samples used was 90 respondents with purposive sampling technique. Data processing was used with multiple linear regression analysis in the SPSS version 20 program. The results showed that there was a partial positive relationship with the atmosphere dimension, namely 0.570, the design dimension, 0.477, and the social dimension, 0.617, to visitor satisfaction. And simultaneously, from the atmosphere dimension, design dimension and social dimension that have been implemented in the Buleleng festival event on visitor satisfaction, it has a strong relationship, which is equal to 0.728.